Finding Meaning in the Organization - Joseph A. Raelin (MIT Sloan Management Review, 2006)
It is axiomatic that people who have a say in the vision underlying any endeavor will be more committed to carrying out that vision than those who are simply given the vision. Indeed, if the vision is handed down, no matter how empowered an employee may be in carrying it out, it may be legitimately resisted because it may not have incorporated local concerns. There is an alternative to top-down vision creation. Visions are preferably co-created in the organization and should arise out of the group as it accomplishes its work. The leader doesn't walk away to create the vision; the vision is often already present. It just needs articulation. This is where the meaning-maker surfaces. Meaning-making is the expression of what group or organizational members are endeavoring to accomplish in their work together. It articulates a collective sense of what the group stands for.
Keywords: M10; M12; M14; M50; M51; M53; 650; Meaning making; Visioning; Community of practice; Leadership; Collaborative leadership; Spirituality